Keir Starmer’s Labor Government: Resetting the UK’s Relations with the European Union - Tatyana N. Cherkashina (СибСкрипт, 2025)
After a 14-year gap, the UK’s Labor government needs to re-establish its post-Brexit ties with the European Union. The author seeks to interpret the early steps made by Prime Minister Keir Starmer in this direction, as well as to understand the internal and external factors that affect the current British foreign policy. To improve its relations with Brussels, the British government intends to reset them, which implies close cooperation in some areas. The article outlines the priority tasks, red lines, and unresolved issues for each side. Relying on the principles of historicism and objectivism, the author used the comparative-historical and problem-chronological methods to explain particular events, actions, meetings, and agreements as part of the reset. The Global Britain strategy depends on global political processes, with a number of objective and subjective factors contributing to the rapprochement of the two sides. For the United Kingdom, the reset of its relations with the European Union is currently more important than improving its special relationship with the United States.